Prediction of crack propagation path in pin loaded lugs using boundary element method - Seet, Raymond Chun Hao (Nanyang Technological University, 2021)
Pin-loaded attachment lug joints are conventionally and widely used in many engineering industries, for their applications. In the aerospace and marine sector, there is heavy usage of pin-loaded attachment lug joints. They are used in general mechanical assemblies to connect major structural components and linkage mechanisms. In these components, cracks are often found at the edge of the pinholes because of high stress concentration. It is vital to understand & evaluate the fracture mechanics of these lug joints with cracks present. This is to detect any early signs of failure to prevent cataclysmal failure from taking place. Stress (stress concentration factor) and fracture (stress intensity factor) analysis are needed to predict the crack propagation path of pin-loaded attachment lug joints. In this report, Boundary Element Method (BEM) is utilized to carry out the investigation. Various parameter conditions such as the geometry of the lug (straight and tapered), loading orientations, outer-to-inner radius ratio of the lugs, and differing crack length sizes were analyzed on the pin-loaded attachment lug. The analysis showed that tapering of lugs and larger outer-to-inner radius ratio of the lugs were essential to slow down crack initiation and propagation. Loading orientations also played an important role in determining the occurrence of cracks.